Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Identification of Genetic Variation Associated With Heat Tolerance in Cowpea ( Vigna unguiculata L. Walp.) - Roland Akakpo; Elaine J. Lee; Jacob B. Pacheco; Esteban F. Rios; Michael B. Kantar; Ousmane Boukar; Kevin M. Volz; Habib Akinmade; Luis Getino; Kenneth J. Boote; María Muñoz‐Amatriaín; Peter L. Morrell (Molecular Ecology, 2026)
Heat tolerance is an important trait in cowpea, a crop that is the primary protein source for a large portion of the human population in sub‐Saharan Africa. Cultivated, landrace, semi‐wild, and wild cowpea grow across the region in diverse climatic conditions. This study used environmental association (envGWAS) and allele‐frequency outlier approaches across a panel of 580 gene bank accessions to identify genomic regions associated with adaptation to heat and limited precipitation. Allele frequency outliers are detected independent of potential selective factors driving differentiation; we used a ranking‐based approach to identify the climate variables most associated with variants among outliers. Precipitation‐related variables dominated the signals we identified for envGWAS and allele frequency outliers. We identified variants on all 11 chromosomes that are putatively associated with cowpea adaptation to higher‐temperature environments. The overlap between variants associated with low precipitation and high temperature suggests that these traits may be inextricably linked in cowpea. The Sahel region is the source of many accessions with derived variants associated with high temperatures, suggesting that accessions from this region could contribute heat tolerance alleles for cowpea improvement.

Surface-based morphometry reveals divergent aging trajectories in veterans with and without traumatic brain injury - Michelle C. Eliason; Amrutha Bindu Nagella; Cristian Cuadra; David S. Wack; Ghazala T. Saleem; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowki; Arthur W. Toga; et al. (GeroScience, 2025)

Vestibular syndrome in dairy heifers associated with Mycobacterium bovis: two case reports and strain characterization - Germán J. Cantón; Yolanda M. Marron; María A. Fiorentino; Eleonora L. Morrell; Juan A. García; María J. Marfil; Facundo Urtizbiria; Claudia Morsella; Karina M. Cirone; María V. Scioli; Martín J. Zumárraga; Fernando Paolicchi (Veterinary Research Communications, 2025)

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Complementary value of molecular, phenotypic, and functional aging biomarkers in dementia prediction - Andreas Engvig; Karl Trygve Kalleberg; Lars T. Westlye; Esten Høyland Leonardsen; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; et al. (GeroScience, 2024)
DNA methylation age (MA), brain age (BA), and frailty index (FI) are putative aging biomarkers linked to dementia risk. We investigated their relationship and combined potential for prediction of cognitive impairment and future dementia risk using the ADNI database. Of several MA algorithms, DunedinPACE and GrimAge2, associated with memory, were combined in a composite MA alongside BA and a data-driven FI in predictive analyses. Pairwise correlations between age- and sex-adjusted measures for MA (aMA), aBA, and aFI were low. FI outperformed BA and MA in all diagnostic tasks. A model including age, sex, and aFI achieved an area under the curve (AUC) of 0.94 for differentiating cognitively normal controls (CN) from dementia patients in a held-out test set. When combined with clinical biomarkers (apolipoprotein E ε4 allele count, memory, executive function), a model including aBA and aFI predicted 5-year dementia risk among MCI patients with an out-of-sample AUC of 0.88. In the prognostic model, BA and FI offered complementary value (both β s 0.50). The tested MAs did not improve predictions. Results were consistent across FI algorithms, with data-driven health deficit selection yielding the best performance. FI had a stronger adverse effect on prognosis in males, while BA’s impact was greater in females. Our findings highlight the complementary value of BA and FI in dementia prediction. The results support a multidimensional view of dementia, including an intertwined relationship between the biomarkers, sex, and prognosis. The tested MA’s limited contribution suggests caution in their use for individual risk assessment of dementia.

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

Transplacental infection by bovine alphaherpesvirus type 1 induces protein expression of COX-2, iNOS and inflammatory cytokines in fetal lungs and placentas - Mercedes M. Burucúa; María A. Risalde; Felipe A. Cheuquepán; Silvina Quintana; Sandra E. Pérez; Germán J. Cantón; Dadin P. Moore; Anselmo C. Odeón; Irene Agulló-Ros; María Valeria Scioli; Claudio Barbeito; Eleonora L. Morrell; et al. (Veterinary Microbiology, 2023)

Barriers and Facilitators to a Healthy Community Environment During COVID-19: Perceptions of Extension Nutrition Educators and Other Key Community Stakeholders - E. Varela; J. Zeldman; A. Kuch; Y. Wang; M. Shushari; E. Hall; J. McNamara; J. Morrell; T. Tolar-Peterson; O. Brown; M. Olfert; L. Franzen-Castle; et al. (Journal of the Academy of Nutrition and Dietetics, 2023)

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Single layer centrifugation (SLC) for bacterial removal with Porcicoll positively modifies chromatin structure in boar spermatozoa - Estíbaliz Lacalle; Estela Fernández-Alegre; Cristina Soriano-Úbeda; Sonia Martínez-Martínez; Juan Carlos Domínguez; J. Ramiro González-Montaña; Jane M. Morrell; Felipe Martínez-Pastor (Theriogenology, 2023)

Rebuilding A Collapsed Bivalve Population, Restoring Seagrass Meadows, and Eradicating Harmful Algal Blooms In A Temperate Lagoon Using Spawner Sanctuaries - Christopher J. Gobler; Michael H. Doall; Bradley J. Peterson; Craig S. Young; Flynn DeLaney; Ryan B. Wallace; Stephen J. Tomasetti; Timothy P. Curtin; Brooke K. Morrell; Elizabeth M. Lamoureux; Berry Ueoka; Andrew W. Griffith; et al. (Frontiers in Marine Science, 2022)
During the past century, bivalve populations across the globe have collapsed, resulting in negative ecosystem consequences due to their outsized impact on shallow estuaries. In response, there has been strong interest in the restoration of marine bivalve populations. Here, we present a decade-long restoration effort that sought to rebuild a collapsed (99.5% reduction in harvest) and recruitment-limited population of hard clams ( Mercenaria mercenaria ) in Shinnecock Bay, NY, USA, using spawner sanctuaries: no-harvest zones where adults were planted at high densities (~27 m- 2 ). Between 2012 to 2019, more than 3.2 million clams were planted in 64 discrete sanctuary plots (~1,850 m 2 each) located in zones with maximal larval retention and sediment and seawater characteristics that would maximize the conditioning and spawning of adults. Hydrodynamic models, quantification of hard clam larvae, and spatial recruitment patterns demonstrated larvae spawned within sanctuaries were transported to regions where clam densities significantly increased 18-fold over seven years (2015-2021; p <0.001) and harvests significantly increased more than 16-fold over nine years (2012-2021; p <0.0001). Increases in populations and harvests were caused by smaller clams recruited within the time frame of the creation of spawner sanctuaries. Higher clam densities caused biological filtration times of the bay to decrease from up to three months at the start of the project to as low as 10 days in 2021. Concurrently, concentrations of the harmful brown tide alga, Aureococcus anophagefferens , and chlorophyll a significantly decreased ( p <0.005) while water clarity and the extent of seagrass beds significantly increased ( p <0.05). Increases in clam landings and improvements in water quality were not observed in adjacent lagoonal estuaries where restoration did not occur. Given these outcomes and the global need for rebuilding marine life, the implementation of spawner sanctuaries using the criteria set forth herein may be a promising approach for restoring hard clam and other bivalve populations in estuaries elsewhere.

Spatial–temporal trends and economic losses associated with bovine abortifacients in central Argentina - Germán J. Cantón; Fabiana Moreno; María A. Fiorentino; Yanina P. Hecker; Maximiliano Spetter; Franco Fiorani; María G. Monterubbianesi; Juan A. García; Erika González Altamiranda; Karina M. Cirone; Enrique L. Louge Uriarte; Andrea E. Verna; et al. (Tropical Animal Health and Production, 2022)

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Modification of plant cell wall chemistry impacts metabolome and microbiome composition in Populus PdKOR1 RNAi plants - Allison M. Veach; Daniel Yip; Nancy L. Engle; Zamin K. Yang; Amber Bible; Jennifer Morrell-Falvey; Timothy J. Tschaplinski; Udaya C. Kalluri; Christopher W. Schadt (Plant and Soil, 2018)

miR-451 limits CD4+ T cell proliferative responses to infection in mice - Lesley M. Chapman; Sara K. Ture; David J. Field; Craig N. Morrell (Immunologic Research, 2017)

Mixed-phenotype grouping: the interaction between oddity and crypsis - Gwendolen M. Rodgers; Helen Kimbell; Lesley J. Morrell (Oecologia, 2013)

RISK‐SENSITIVE ANTIPREDATOR BEHAVIOR IN THE TRINIDADIAN GUPPY, POECILIA RETICULATA - M. S. Botham; R. K. Hayward; L. J. Morrell; D. P. Croft; J. R. Ward; I. Ramnarine; J. Krause (Ecology, 2008)
The comparative approach has become a powerful tool for understanding how predation has shaped prey behavior. In this study we recorded the occurrence of common aquatic predator species and their densities in seven natural populations of Trinidadian guppies, Poecilia reticulata . We then exposed shoals of guppies from each of these populations to a series of predator treatments. Predator treatments differed in the species of predator used (pike cichlids, Crenicichla frenata ; rivulus, Rivulus hartii ; and freshwater prawns, Macrobrachium carcinus ) and thus in the level of risk posed. We recorded the antipredator responses of guppies in each of these predator treatments. The strength of antipredator behavior shown by guppies was affected by both the type of predator they were exposed to and the level of predation risk they experienced naturally in the wild. Importantly, we found that guppies from high‐risk populations showed a heightened response, compared to those from lower risk populations, only when exposed to the predator species that posed the greatest risk. Our results show the importance of individual predator species in shaping the behavioral traits of prey species at the population level. This has implications for prey movement between habitats that are geographically close but differ greatly in predator fauna.

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Air temperatures at Armagh Observatory, Northern Ireland, from 1796 to 2002 - C. J. Butler; A. M. García Suárez; A. D. S. Coughlin; C. Morrell (International Journal of Climatology, 2005)
Three independent mean temperature series for Armagh Observatory, covering the period 1796–2002 have been calibrated and corrected for the time of reading and exposure. Agreement between the three series is good in regions of overlap. With a short gap in the Armagh data from 1825 to 1833 filled by data from two stations in Dublin, the resulting series is the longest for the island of Ireland and one of the longest for any single site in the British Isles. Over the past 207 years, we note that temperatures in Armagh, in all seasons, show a gradual overall trend upwards. However, there are seasonal differences: summer and spring temperatures have increased by only half as much as those in autumn and winter. This is partly due to the exceptionally cold winters and autumns experienced prior to 1820. Relative to the overall trend, warm periods occurred in Ireland, as in other parts of Europe, in the mid‐19th century, in the mid‐20th century and at the end of the 20th century. Relatively cool temperatures prevailed in the early 19th century, in the 1880s and in the 1970s. Thus, if the baseline against which current temperatures are compared were moved from the late 19th century to include the earlier warm period, the apparent warming at the end of the late 20th century would be correspondingly reduced. A gradual decline in the daily temperature range at Armagh since 1844 may have resulted from higher minimum temperatures associated with increased cloudiness. A 7.8 year periodicity is identified in winter and spring mean temperatures at Armagh, which is probably a consequence of the North Atlantic oscillation. Copyright © 2005 Royal Meteorological Society

Crop‐to‐weed introgression has impacted allelic composition of johnsongrass populations with and without recent exposure to cultivated sorghum - P. L. MORRELL; T. D. WILLIAMS‐COPLIN; A. L. LATTU; J. E. BOWERS; J. M. CHANDLER; A. H. PATERSON (Molecular Ecology, 2005)
Sorghum halepense L. (johnsongrass) is one of the world's most noxious weeds, and a paradigm for the potential dangers of crop–weed hybridization. Introduced into the southeastern United States about 200 years ago, S. halepense is a close relative of cultivated sorghum ( Sorghum bicolor ). Both artificial crossing and experimental field studies have demonstrated the potential for S. halepense × S. bicolor hybrid formation, but no prior study has addressed the long‐term persistence of sorghum genes in johnsongrass populations. We surveyed 283 loci (on all 10 sorghum linkage groups) to identify 77 alleles at 69 loci that are found in US sorghum cultivars but are absent from a worldwide sampling of johnsongrass genotypes. These putatively cultivar‐specific alleles were present in up to 32.3% of individuals in johnsongrass populations adjacent to long‐term sorghum production fields in Texas and Nebraska. Lower frequencies of cultivar‐specific alleles at smaller numbers of loci are found in johnsongrass populations from New Jersey and Georgia with no recent exposure to cultivated sorghum, suggesting that introgressed sorghum alleles may be dispersed across long distances. The number of cultivar‐specific alleles and extensive multilocus patterns of cultivar‐specific allelic composition observed at both linked and unlinked loci in the johnsongrass populations, are inconsistent with alternatives to introgression such as convergence, or joint retention of ancestral polymorphisms. Naturalized johnsongrass populations appear to provide a conduit by which transgenes from sorghum could become widely disseminated.

Intercontinental dispersal: The origin of the widespread South American plant speciesGilia laciniata (Polemoniaceae) from a rare California and Oregon coastal endemic - P. L. Morrell; J. M. Porter; E. A. Friar (Plant Systematics and Evolution, 2000)